2020
DOI: 10.36713/epra4518
|View full text |Cite
|
Sign up to set email alerts
|

Public Reaction to Covid-19 on Twitter: A Thematic Analysis

Abstract: Emergency situations typically lead to a plethora of public attention on social media platforms like ‘Twitter’. Twitter provides a unique opportunity for public health researchers to analyze untampered information shared during a disease outbreak. Considering the ongoing public health emergency, we conducted a study investigating the public reaction to COVID-19 pandemic around the world using in-depth thematic analysis of Twitter data. A dataset of 212846 tweets was retrieved over a period of seven days (from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Three studies proposed that social media should be supervised by an authority or government: 10 , 19 , 26 misinformation could be addressed by the government providing more comprehensive reports on the current epidemiological situation. Three studies suggested introducing policies or regulations for social media, 20 , 27 , 29 and two mentioned the need for more research. 22 , 23 Six studies did not suggest any solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies proposed that social media should be supervised by an authority or government: 10 , 19 , 26 misinformation could be addressed by the government providing more comprehensive reports on the current epidemiological situation. Three studies suggested introducing policies or regulations for social media, 20 , 27 , 29 and two mentioned the need for more research. 22 , 23 Six studies did not suggest any solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Organizational Policy . Social media can be useful for communicating accurate health information during a public health crisis (Chou et al, 2018; Mustafa et al, 2020; Yuksel & Cakmak, 2020). Health services organizations can leverage these tools by implementing policies that promote communication of evidence-based information from trusted sources on social media, for example, by recording videos with accurate information about COVID-19 vaccination and posting them on social media (CDC, 2021a; Chou et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…According to a current paper (Mustafa, Ansari, Mohanta & Balla, 2020) humor, although not the dominant form of public response to the pandemic, was a very noticeable trend, for example on Twitter. Moreover, in an analysis of TikTok videos that circulated under the hashtag #Corona, it was found that besides (supposedly) enlightening, informative, documentary and racist stigmatizing videos there were humorous videos among the 100 most popular clips (Ackermann, Dewitz & Makulik, 2020).…”
Section: Introductionmentioning
confidence: 95%